Making the grade - Wardrop, Ken (El Segundo, CA : Gravitas Ventures, 2018)
Explores the world of the piano lessons in Ireland, where every year students prepare to pass graded musical exams in order to advance to the next proficiency level.
Originally released as a motion picture in 2017.
MPAA rating: Not rated.
DVD, wide screen 1.85:1.
Closed-captioned.
Keywords: Piano -- Instruction and study -- Ireland; Music -- Instruction and study -- Ireland; Piano -- Examinations -- Ireland; Music -- Examinations -- Ireland; Films for the hearing impaired; Documentary films; Nonfiction films